Encyclopaedia of life sciences - O'Daly, Anne (New York Marshall Cavendish, 1996)
v.v.4 Dimorphism-Extinction--5 Eyes-Grains------systems---v.10 Stomach-Zoology
v.1: Abdomen-Biennial plants
v.2 Biochemistry-Chemotherapy--systems-
v.3: Child development-Digestive
v.4: Dimorphism-Extinction
v.6: Grasses-Larvae--systems
v.7: Leaf crops-muscular
Keywords: Life sciences--Encyclopedias; Biology--Encyclopedias; Biology--Encyclopedias,Juvenile